ADAPTASI KOMUNIKASI ANTARBUDAYA MAHASISWA ASAL BATAM DALAM MENGHADAPI GEGAR BUDAYA DI JIMBARAN PROVINSI BALI - Siagian, Astika Dame Uli; Arjawa, I Gusti Putu Bagus Suka; Ranteallo, Ikma Citra (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 5 No 1 (2025): JISSOROT, 2025)
Migrant students, especially students from Batam who continue their studies in Jimbaran, Bali Province, often face challenges in the adaptation process, especially intercultural communication. Cultural differences trigger culture shock that causes students to have difficulty adapting. This study aims to analyze the intercultural communication adaptation of students from Batam in facing culture shock and to explain the intercultural communication barriers faced by students from Batam during the adaptation process in Jimbaran, Bali Province. This research method uses a qualitative approach of descriptive type and the theory chosen as a scalpel to analyze this research is the theory of communication accommodation by Howard Giles. The results showed that the intercultural communication adaptation of students from Batam in facing culture shock took place through four cultural adaptation processes with the U-Curve model by Martin and Nakayama. The honeymoon phase, experiencing pleasant feelings when they first entered and were impressed with the things they met in Jimbaran. The frustration phase, they experience culture shock due to differences in language and accent, food tastes, customs, and lifestyles that cause discomfort and misunderstanding. The readjustment phases, students from Batam began to readjust themselves by learning and following Balinese language and accent, adjusting local food tastes, mingling with Balinese students and communities, and participating in traditional Balinese cultural activities in Jimbaran. In the resolution phase, the finally accepted the new culture and were comfortable. Then the intercultural communication barriers faced by them during the adaptation process are language differences that are difficult to understand, stereotypes and prejudices, and differences in culture and habits. Therefore, to fase the challenges of intercultural communication by using convergence strategies.